First-principles prediction of high-entropy-alloy stability. (December 2017) - Feng, Rui; Liaw, Peter; Gao, Michael; Widom, Michael
Abstract High entropy alloys (HEAs) are multicomponent compounds whose high configurational entropy allows them to solidify into a single phase, with a simple crystal lattice structure. Some HEAs exhibit desirable properties, such as high specific strength, ductility, and corrosion resistance, while challenging the scientist to make confident predictions in the face of multiple competing phases. We demonstrate phase stability in the multicomponent alloy system of Cr–Mo–Nb–V, for which some of its binary subsystems are subject to phase separation and complex intermetallic-phase formation. Our first-principles calculation of free energy predicts that the configurational entropy stabilizes a single body-centered cubic (BCC) phase fromT = 1700 K up to melting, while precipitation of a complex intermetallic is favored at lower temperatures. We form the compound experimentally and confirm that it develops as a single BCC phase from the melt, but that it transforms reversibly at lower temperatures. High entropy alloys: predicting phase stability High entropy alloys with four species or more can be single phase solid solutions but can equally phase separate, making their design difficult. A collaboration led by Michael Widom at Carnegie Mellon University used free energy calculations paired with hybrid Monte Carlo molecular dynamics simulations to predict the separation of a Cr–Mo–Nb–V alloy from a stable single phase body-centered cubic solid solution at high temperature to a separated intermetallic Laves phase at lower temperatures. By synthesizing the alloy and annealing it at different temperatures, the authors confirmed the phase separation and showed that it was reversible. Combining quantum-mechanical total energy calculation with statistical mechanics to predict free energies is therefore an effective avenue that may be applied to many problems in alloy design.